The visual languange of design (Educational Video Network, 1993)
Uses a wide variety of paintings from several museums to illustrate the basic concepts of artistic structure and design. The second tape uses paintings to illustrate and describe the characteristics of painting styles from classical and Byzantine through Cubism, Dadaism, pop art and fold art.